Neutrophil lymphocyte ratio as useful predictive tool for glycaemic control in type 2 diabetes: retrospective, single center study in Turkey - Yuksel Salduz, Zeyneb Irem; Ozder, Aclan; admin (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the inflammatory cells in the complete blood count test and their relationship with the glycaemic control in type 2 diabetes patients. —Continue